THE APPLICATION OF DEMONSTRATION METHODS IN LEARNING EXPLANATION TEXT MIDDLE SCHOOL STUDENTS: CLASS ACTION RESEARCH - Muhajir, Ahmad (Al'Adzkiya Journal, 2020)
Abstract: The purposes of this research are to improve: (1) learning process quality and, (2) students skill of writing explanation text using demonstration method. This research was held at Senior High School XI Persiapan Stabat. The results of this research are: 1) demontration method can improving process quality of writing exlanation text learning of XI Science 2 of Senior High School 1 Swasta Persiapan Stabat in Academic Year of 2020/2021 that shown by improved teacher and students performance. The average value of teacher performance in cycle I is 70,83 (enough) and in cycle II is 81,05 (good). Then average value of students performance in cycle I is 59,3 (bad) and in cycle II is 81,16 (good); (2) the demonstration method can improve students skill of explanation text writting of XI Science 2 of Senior High School Swasta Persiapan Stabat in Academic Year of 2020/2021 that shown on achive of value minimum completeness, that is 75. The average of students skill of writing explanation text in cycle I is 74,7 with percentage of 62,5% and in cycle II is 82,3 with percentage of 90,9 %.